Wybrane problemy oceny zmian w procedurach i mechanizmach kontroli wewnętrznej w bankach - Niewiadoma, Maria (Changes in Procedures and Mechanisms of Internal in Banks, 2008)
The financial sector plays a significant role in the national economy. Its key role is the internal control in banks. The paper presents aims of internal control in banks. The author explains the elements of procedures and actions of internal control which have been changed in Poland during the last years.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (6); 2008; nr 1196, s. 113-121